General Tendencies in Modern Economy: Sustainable Development and Green Economy - RUDNEVA, Larisa Nikolaevna; PCHELINTSEVA, Irina Gennadievna; GURYEVA, Maria Andreevna (Journal of Environmental Management and Tourism, 2016)
The article overviews general questions on development of two key tendencies in modern economy over the last decades - sustainable development and “green” economy. The paper defines the terms “green” economy, discovers its main characteristics, discusses its concepts and provides its evaluation, as well as predicts its development perspectives.
Keywords: sustainable development; “green” economy; aspects of sustainable development; index of “green” economy